Alcohol consumption and risk of type 2 diabetes in European men and women: Influence of beverage type and body sizeThe EPIC-InterAct study - Beulens, J; Van der Schouw, Y; Bergmann, M; Rohrmann, S; Schulze, M; Buijsse, B; Grobbee, D; Arriola, L; Cauchi, S; Tormo, S; Allen, N; van der A, D; et al. (2012)
Objective: To investigate the association between alcohol consumption and type 2 diabetes, and determine whether this is modified by sex, body mass index (BMI) and beverage type. Design: Multicentre prospective case-cohort study. Setting: Eight countries from the European Prospective Investigation into Cancer and Nutrition cohort. Subjects: A representative baseline sample of 16154 participants and 12403 incident cases of type 2 diabetes. Interventions: Alcohol consumption assessed using validated dietary questionnaires. Main outcome measures: Occurrence of type 2 diabetes based on multiple sources (mainly self-reports), verified against medical information. Results: Amongst men, moderate alcohol consumption was nonsignificantly associated with a lower incidence of diabetes with a hazard ratio (HR) of 0.90 (95% CI: 0.78-1.05) for 6.1-12.0 versus 0.1-6.0gday-1, adjusted for dietary and diabetes risk factors. However, the lowest risk was observed at higher intakes of 24.1-96.0gday-1 with an HR of 0.86 (95% CI: 0.75-0.98). Amongst women, moderate alcohol consumption was associated with a lower incidence of diabetes with a hazard ratio of 0.82 (95% CI: 0.72-0.92) for 6.1-12.0gday-1 (P interaction gender <0.01). The inverse association between alcohol consumption and diabetes was more pronounced amongst overweight (BMI≥25kgm-2) than normal-weight men and women (P interaction<0.05). Adjusting for waist and hip circumference did not alter the results for men, but attenuated the association for women (HR=0.90, 95% CI: 0.79-1.03 for 6.1-12.0gday-1). Wine consumption for men and fortified wine consumption for women were most strongly associated with a reduced risk of diabetes. Conclusions: The results of this study show that moderate alcohol consumption is associated with a lower risk of type 2 diabetes amongst women only. However, this risk reduction is in part explained by fat distribution. The relation between alcohol consumption and type 2 diabetes was stronger for overweight than normal-weight women and men. © 2012 The Association for the Publication of the Journal of Internal Medicine.